(untitled) (Raparin Journal of Humanities (RJH), 2023)
Water balances in any area are one of the main factors affecting water revenue, the natural environment, and vegetation cover. Water balance refers to the contribution of rainfall, temperature, evaporation, and impact on surface and groundwater in each region. In this research, an analytical and descriptive method was used to analyse the climate data used at Dukan climate station to determine the total amount of water between (2000-2022), which reached (1714.6 mm) For nine (9) months of the year, we have a shortage of water; only three (3) months have surpluses of water, which reached 130.1 mm. To prove whether the evaporation taken from Dukan climate station is the true evaporation of the water balance in the study area, we used the Thornthwaite equation to find out the true water balance based on temperature and annual rainfall for the same period. The results showed that the area had a water shortage of (1287.3 mm) for six (6) months and a surplus of (390.5 mm) for six (6) months. At the same time, the total evaporation, or evapotranspiration, reached (1461.9 mm). Based on the water balance equation, using scientific resources, and showing the relationship between precipitation and evaporation, the research concluded that the water balance varies from year to year depending on the amount of rainfall in the study area, but in general there is a water shortage in the study area during the year, and the highest water shortage in the region is in the summer months.